Epidemiology and patterns of facial fractures due to road traffic accidents in Taiwan: A 15-year retrospective study. (3rd October 2017) - Yang, Cheng-San; Chen, Solomon Chih-Cheng; Yang, Yung-Cheng; Huang, Li-Chung; Guo, How-Ran; Yang, Hsin-Yi
ABSTRACT: Objective : The facial region is a commonly fractured site, but the etiology varies widely by country and geographic region. To date, there are no population-based studies of facial fractures in Taiwan. Methods : We conducted a retrospective study of patients diagnosed with facial fracture and registered in the National Health Insurance Research Database of Taiwan between 1997 and 2011. The epidemiological characteristics of this cohort were analyzed, including the etiology, fracture site, associated injuries, and sex and age distributions. Results : A total of 6, 013 cases were identified that involved facial fractures. Most patients were male (69.8%), aged 18–29 years (35.8%), and had fractures caused by road traffic accidents (RTAs; 55.2%), particularly motorcycle accidents (31.5%). Falls increased in frequency with advancing age, reaching 23.9% among the elderly (age > 65 years). The most common sites of involvement were the malar and maxillary bones (54.0%), but nasal bone fractures were more common among those younger than 18 years. Conclusion : Most facial injuries in Taiwan occur in young males and typically result from RTAs, particularly involving motorcycles. However, with increasing age, there is an increase in the proportion of facial injuries due to falls.